2018
DOI: 10.1261/rna.065136.117
|View full text |Cite
|
Sign up to set email alerts
|

The life of U6 small nuclear RNA, from cradle to grave

Abstract: Removal of introns from precursor messenger RNA (pre-mRNA) and some noncoding transcripts is an essential step in eukaryotic gene expression. In the nucleus, this process of RNA splicing is carried out by the spliceosome, a multi-megaDalton macromolecular machine whose core components are conserved from yeast to humans. In addition to many proteins, the spliceosome contains five uridine-rich small nuclear RNAs (snRNAs) that undergo an elaborate series of conformational changes to correctly recognize the splice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
107
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(111 citation statements)
references
References 273 publications
(423 reference statements)
4
107
0
Order By: Relevance
“…Early work to identify and characterize snRNA genes revealed that U1 and U2 snRNA genes are present as both large multi-copy clusters and pseudogenes of similar sequence spread throughout the genomes of many model organisms (Denison et al, 1981;Denison and Weiner, 1982;Lindgren et al, 1985;Lund and Dahlberg, 1984;Manser and Gesteland, 1982;Van Arsdell and Weiner, 1984). Later, conserved sequence elements were discovered in the promoters of all canonical snRNA genes, and all major snRNAs were discovered to be transcribed by RNA polymerase II (Pol II), except U6 snRNA which is transcribed by RNA polymerase III (reviewed in Didychuk et al, 2018;Guiro and Murphy, 2017). Identification of sequence heterogeneity of U1, U4, and U5 suggested that snRNA variants could be differentially expressed, and it was hypothesized that expression of low abundance snRNAs may regulate alternative splicing (Branlant et al, 1983;Forbes et al, 1984;Krol et al, 1981;Lund, 1988;Lund and Dahlberg, 1987;Sontheimer and Steitz, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Early work to identify and characterize snRNA genes revealed that U1 and U2 snRNA genes are present as both large multi-copy clusters and pseudogenes of similar sequence spread throughout the genomes of many model organisms (Denison et al, 1981;Denison and Weiner, 1982;Lindgren et al, 1985;Lund and Dahlberg, 1984;Manser and Gesteland, 1982;Van Arsdell and Weiner, 1984). Later, conserved sequence elements were discovered in the promoters of all canonical snRNA genes, and all major snRNAs were discovered to be transcribed by RNA polymerase II (Pol II), except U6 snRNA which is transcribed by RNA polymerase III (reviewed in Didychuk et al, 2018;Guiro and Murphy, 2017). Identification of sequence heterogeneity of U1, U4, and U5 suggested that snRNA variants could be differentially expressed, and it was hypothesized that expression of low abundance snRNAs may regulate alternative splicing (Branlant et al, 1983;Forbes et al, 1984;Krol et al, 1981;Lund, 1988;Lund and Dahlberg, 1987;Sontheimer and Steitz, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…U2-U6 and U4-U6 snRNAs are critical structural elements of the spliceosome that are rich in Nm modifications (3). These snRNAs undergo changes in secondary structure and base-pairing which are essential for the assembly and disassembly of the spliceosome as well as in cycling between different conformational states required for catalysis (49,50). Nm modifications in the active core of the spliceosome U2-U6 snRNA complex have been shown to promote a conformational transition between a three-way and four-way junction proposed to aid correct positioning of pre-mRNA for exon ligation (51).…”
Section: Introductionmentioning
confidence: 99%
“…The Lsm2-8 complex shares 6 out of 7 subunits with Lsm1-7, localizes in the nucleus, and binds the 3' ends of U6 and U6 atac snRNAs (25)(26)(27)(28). U6 snRNA is transcribed by RNA polymerase III, which terminates transcription after synthesis of an oligoU tail at the end of U6 snRNA (29). This tail can then be elongated by the enzyme Tutase (29).…”
Section: Introductionmentioning
confidence: 99%
“…U6 snRNA is transcribed by RNA polymerase III, which terminates transcription after synthesis of an oligoU tail at the end of U6 snRNA (29). This tail can then be elongated by the enzyme Tutase (29). Finally, U6 snRNA is processed by the 3′-5′ exoribonuclease Usb1 (29), resulting in a 2′,3′ cyclic phosphate in most organisms (30) (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation